The Solar Tracker Prototype Based on Arduino Uno - Setiyono Setiyono; Kunto Wibowo (Jurnal Ecotipe (Electronic, Control, Telecommunication, Information, and Power Engineering), 2024)
The placement of solar panels to capture solar energy is generally installed in a certain and fixed position (static). The dynamic change in the sun's position from east to west at any time means that the solar panels absorb less energy. So, installing an automatic driving device on the solar panel to adjust its perpendicular position to the sun's rays is very necessary. This Solar Tracker tool has 4 light sensors that function to identify the intensity of sunlight as a signal entered by the Arduino Uno microcontroller. This information is then processed to become a signal to drive horizontal and vertical servo motors. The shaft of this motor is connected to the mechanical circuit of the solar panel via a gearbox to carry out movement. A comparator will compare sunlight information and a reference voltage to control the rotation of the servo motor which can determine the time needed for the motor to rotate or stop. The research results on solar panels using a tracker were that the best voltage and current values were obtained between 12.00 – 13.00 WIB with an average voltage value of 11.45 V and an average current value of 0.49A.